Pengembangan Media Pembelajaran Berbasis Android Dalam Bentuk Aplikasi E-Waris Mata Pelajaran Fiqih Dengan Materi Mawaris - Hidayatulloh, Muhammad Kris Yuan; Nariswari, Nadya Ruri; Putra, Ino Angga (JoEMS (Journal of Education and Management Studies), 2023)
This study aims to develop fiqh learning media with an android-based e-waris application with mawaris material for class XI MAN student and determine the feasibility of e-waris application based on assessment of material experts, media exsperts, and responses from student. Development (R&D) which was adepted from the ADDIE development model.There are 3 stage, namely : 1) analysis, 2) Design, 3) Development. Validation is carried out by material expert and media experts. The developed media was tested on 42 student of class XI IPA MAN 9 Jombang. The result showed that the feasibility level of the fiqh learning media with the android-based e-waris application as a learning medium was based on the assessment : 1) material experts obtained a total score of 68.00 which was included in the “Good” category and if it was a percentage, it score 77.28%, so that including the “Decent” category, 2) media experts obtained a total score of 104.00 which is included in the “Good” category and if it is a percentage it gets a score of 76.48%, so it is included in the “Decent” category. Student responses to this media at the times of the trial get a percentage of 82.33%. this the fiqih learning media with the android-based e-waris application is appropriate to be used as a fiqih learning medium for mawaris material in schools.